EFFECT OF ANNEALING ON Cu-Nb-Sn SUPERCONDUCTING WIRE - Agung Imaduddin; Bintoro Siswayanti; Andika Widya Pramono; Pius Sebleku; Hendrik Hendrik; Sigit Dwi Yudanto (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2015)
EFFECT OF ANNEALING ON Cu-Nb-Sn SUPERCONDUCTING WIRE. The most common application of superconductors is done in the form of superconducting wire. Among the existing types of superconductors, Cu-Nb-Sn superconductors are the most widely used as a wire, producing a high magnetic field. But the critical temperature (TC) values of its superconductors are low enough so that the resulting magnetic field and its application fields are limited. In this study we investigated the effect of annealing treatment on the Cu-Nb-Sn superconducting wire. Note that the process of annealing on superconducting wire can increase the value of the critical temperature of 8K to 16K. The increase is predicted because of the forming of Nb3Sn compounds, and the Nb3Sn compound becomes more stable.Annealing processes were performed at temperatures ranging from 873K to 1173K as well as various annealing time from 32 hours to 120 hours. The superconductivity of the samples were analyzed using resistivity measurement by cryogenic system under low temperature condition. The annealing can be performed optimally at the temperature of 873K for 72 hours when TC reaches 16K. However, the purity of the conductivity properties obtained at the optimal annealing temperature at 723K for 72 hours.